(untitled) (Philological Studies, 2019)
This paper gives insight into the reflections of Isidora Sekulić on Oton Župančič’s Ciciban, as well as poetry for children in general, with respect to interdialogic relations holding between important themes of her essayism (perception of the aesthetic and engaged, the oral tradition, folk spirit and phenomenon of national in art) in the context of poetic demarcation of the literature for children of the thirtieth years of the twentieth century.